Keputusan Pemilihan Kosmetik Halal Generasi Milenial dengan Pendekatan Theory Reasoned Action (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of religiosity, halal knowledge, halal certification, and subjective norms on customer loyalty toward halal cosmetic products of the Wardah brand, with customer satisfaction as a mediating variable. The background of this research stems from the growing awareness among Muslim consumers—particularly millennials—of the importance of using cosmetic products that comply with halal principles. A quantitative approach was employed using a survey method. A total of 185 respondents, who are Wardah users in Tangerang Regency, were selected through purposive sampling. Data were analyzed using SEM  with the AMOS 29. The results reveal that halal knowledge and halal certification have a significant positive effect on both customer satisfaction and loyalty. Meanwhile, religiosity and subjective norms do not significantly influence satisfaction, and religiosity even shows a negative effect on loyalty. Customer satisfaction is proven to mediate the relationship between religiosity and loyalty, as well as between subjective norms and loyalty; however, it does not mediate the relationship between halal knowledge and loyalty. These findings imply that in order to build long-term customer loyalty in the halal cosmetic market, companies must go beyond religious imagery and formal certification. Instead, they should focus on consumer education, consistent product quality, and delivering brand experiences that align with the emotional and spiritual values of Muslim consumers.